Uso de nanospray dryer para carreamento de α-galactosilceramida em nanopartículas poliméricas: um processo de etapa única para melhorar a resposta de linfócitos Natural Killer T invariantes - Gonzatti, Michelangelo Bauwelz [UNIFESP] (2019)
Invariant Natural Killer T (iNKT) lymphocytes modulate several immunological responses, especially upon their activation by α-Galactosylceramide (αGC). Although their exogenous stimulation results in potent anti-tumor activities in experimental models, modest effects are observed in clinical trials. Thus, to improve the biological activity of αGC, different studies focused in the vectorization of the agonist in PLGA and/or PEG-based nanoparticles. Despite promising findings, these approaches require several steps, from solvent decontamination through extrusion in membrane systems. Here in, we demonstrate a novel, single step, process to vectorize αGC in a cationic copolymer based on dimethylaminoethyl methacrylate, butyl methacrylate and methyl methacrylate (DBM), using a nano spray dryer. The vectorization of αGC in DBM nanoparticles enhanced in vitro and in vivo biological activity. The administration of DBM nanoparticles improved the IFN-γ production, increased αGC loading onto CD1d molecules and was able to successfully control the development of lung metastatic nodules in B16F10 model. Thus, we propose that vectorization of αGC DBM polymeric nanoparticles using nanospray dryer technology is an alternative approach to improve iNKT-based immunotherapy.